Exhaust emission characteristics of gaseous low-temperature biomass fuel in spark-ignition engine. (5th September 2016) - Chen, Lei; Song, Peng; Zeng, Wen; Zhang, Jing; Feng, Chao; Ma, Hongan
Highlights: Combustion and emission tests of bio-gas engine were carried out. The effect of fuel components on engine performance were comprehensive analyzed. The ideal operation has been obtained by using component-control methods of biogas. Abstract: This paper presents the results of research on the combustion and emission characteristics of synthetic bio-gas in a spark-ignition engine. The combustible gas components methane, hydrogen and carbon monoxide as well as the diluted gas component carbon dioxide are employed to simulate actual bio-gas which is produced through a low-temperature gasification technique. The effects of fuel components, equivalence ratio, fuel substitution and dilution on combustion and emission characteristics were investigated. The results show that CO2 dilution gives little variation in brake thermal efficiency at a low dilution ratio, but there is clearly a reduction in brake thermal efficiency at a high dilution ratio. The NOX emission of individual fuels also decreases with the dilution ratio because there is less input heat. However, a high CO2 content also leads to deterioration in the stability of engine operation and a high CO emission level. The substitution of H2 improves brake thermal efficiency and engine stability, which offsets the adverse effects, to a certain extent, of dilution with CO2 dilution at a high dilution ratio. By utilizing a component-controlling strategy, it is possible to use bio-gas to obtain ideal engine operation gas with acceptable brake thermal efficiency and NOX emissions.